The Third Generation University in the Context of the Fourth Industrial Revolution - Duc, Nguyen Huu (VNU Journal of Science: Education Research; Vol 36 No 1, 2020)
This study identifies the organizational and academic characteristics of the three generations of world universities and their two transition periods. In particular, from the second-generation university (2GU) to the third-generation university (3GU), the higher education institutions have developed from a closed level to an open and flexible level of training and from single disciplines to interdisciplinary research and innovation. In terms of these academic aspects, 3GU is an iterative development of the characteristics of 1GU university, but at a higher level, more comprehensive and more thorough. About the organization, with the proposed 90-degree rotation matrix structure, the 2GU university can move from a centralized and bureaucratic management model to a high autonomy one. The subsidized financial mechanism has shifted to a competency-based competition mechanism. With that transformation, the 3GU generation university can both meet its mission as well as the requirements of industrial revolution 4.0. In particular, with the way the budget is organized into four ﬂows of ﬁnance, the 3GU university can completely break with the direct attentions of the government. Universities become fully independent organizations with autonomy in defining their rules of operation. Instead of trying to ensure quality with its own control, the government can let the university system operate on a market competitive mechanism.